Характеристика протизапальної та знеболюючої активності ібупрофену та його комбінації з вінбороном на моделі ад’ювантного артриту у щурів - Гладких, Ф.В.; Степанюк, Н.Г. (Вісник наукових досліджень. 2015. № 2 (79). С. 108–111, 2015)
Експериментально встановлено, що комбінації ібупрофену з вінбороном притаманна більша за величиною протизапальна та знеболююча дія при ад’ювантному артриті у щурів, ніж при монотерапії вказаним антифлогістиком, за рахунок потенціюванню фармакологічних ефектів обох препаратів. Крім того зазначена комбінація сприяє підвищенню безпечності ібупрофену. /// It is known that non-steroidal antiinflammatory drugs (NSAIDs) have antiinflammatory effects of a wide spectrum - they are able to reduce the expression of inflammatory reaction of any etiology, location and nature of any leakage, inhibiting both processes exudation in acute inflammation and proliferative activity of fibroblasts in chronic inflammation. However, all members of this class of drugs are common so-called class-specific side effects. Therefore, one of the pressing problems of NSAID drug therapy is to increase their safety. PURPOSE: to provide a comparative assessment of anti-inflammatory and analgesic action of ibuprofen and its combination with vinboron in adjuvant arthritis in rats. MATERIALS AND METHODS The study was conducted on 28 mature male rats, divided into 4 groups: I - intact rats (n=7), II - rats with simulated adjuvant arthritis (AA) untreated (control), III - rats with AA (n=7), treated with ibuprofen (218 mg/kg), IV- rats with AA (n=7) treated with ibuprofen (218 mg/kg) in combination with vinboron (11 mg/kg). RESULTS AND DISCUSSION Treatment of AA combination with ibuprofen and vinboron led to a distinct anti-inflammatory effect of ibuprofen through potentiation of the pharmacological effect of both drugs. This is evidenced by statistically significant reduction of inflammatory reaction in damaged limbs of animals in the study group compared with the 14 day of experiment, and even more expressive suppression of the inflammatory response compared with monotherapy ibuprofen. Thus, combination therapy ibuprofen and vinboron resulted in statistically significant inhibition of the inflammatory response 18,6% compared to day 14 of the experiment, which is 7,4% higher than the same indicator monotherapy ibuprofen. Also found that the most pronounced changes in pain threshold were recorded in the group of animals treated with a combination of ibuprofen and vinboron 14 days of the experiment. The increase pain threshold by 28 days of the experiment group combination with ibuprofen and vinboron statistically significantly higher than the corresponding figures twice as monotherapy ibuprofen and accounted for 15,9% and 39.2%. This shows the ability vinboron potentiate the analgesic effect of ibuprofen by the presence of his anti-inflammatory, analgesic and antispasmodic activity. CONCLUSIONS In assessing the results of the survey, it concludes that the combination of ibuprofen and vinboron inherent larger in size inflammatory and analgesic action in adjuvant arthritis in rats than monotherapy specified NSAID. This is evident increase in anti-inflammatory action of ibuprofen in the area of the damaged joint and increase pain threshold, through potentiation of the pharmacological effects of both drugs. Also mentioned combination improves safety of ibuprofen.
Гладких Ф. В., Степанюк Н. Г. Характеристика протизапальної та знеболюючої активності ібупрофену та його комбінації з вінбороном на моделі ад’ювантного артриту у щурів. Вісник наукових досліджень. 2015. № 2 (79). С. 108–111 DOI: http://dx.doi.org/10.11603/2415-8798.2015.2.5617. Режим доступу: http://nbuv.gov.ua/UJRN/vndt_2015_2_33